A Desktop-Based Digital Image Encryption System Using The Lorenz Chaotic Map - Makmun Makmun (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The increasing use of digital images in communication, healthcare, and information systems has raised the need for effective image security mechanisms. Conventional encryption methods are often less suitable for image data because of its large size and high correlation among adjacent pixels. Therefore, chaos-based cryptography has gained attention due to its sensitivity to initial conditions and ability to generate highly random sequences. This study aims to develop and evaluate a desktop-based digital image encryption application using the Lorenz System Chaotic Map to ensure image confidentiality and accurate reconstruction. This study employed a quantitative experimental approach in the form of a computational experiment. Data were collected through direct testing using RGB and grayscale images with different dimensions and formats, including .jpg, .png, and .bmp. The system was implemented in a desktop environment and evaluated using processing time, histogram analysis, Mean Squared Error (MSE), Peak Signal-to-Noise Ratio (PSNR), and key sensitivity analysis. The results show that the proposed system successfully transformed original images into visually unrecognizable encrypted images and reconstructed them perfectly during decryption. The encrypted images exhibited more uniform histogram distributions and low PSNR values, while the decrypted images showed zero MSE and infinite PSNR, indicating lossless recovery. The system also demonstrated high sensitivity to small key changes. These findings imply that the proposed method is effective for digital image protection in practical applications. The originality of this study lies in integrating a Lorenz-based encryption algorithm into a user-oriented desktop application equipped with built-in evaluation features.